Low-cost, open-source, variable speed and incline treadmill for studying impacts of neonatal locomotion. (April 2020) - Williams, Mitchell; Sater, Stuart; Burkhalter, Colin; Schoonen, Stephen; Miller, Jacob; Shrestha, Dev; Brumley, Michele R.; Schiele, Nathan R.
Graphical abstract: Abstract: There is a need for a small-scale, laboratory treadmill to investigate impacts of neonatal locomotion on neuromuscular and musculoskeletal development in small animal models. Adult mice and rats are routinely assessed using commercially available treadmills, but these treadmills can be relatively expensive and they may lack features needed to evaluate developing animals. Therefore, to overcome these limitations, a new treadmill was designed, built and calibrated. This open-source treadmill was designed specifically for neonatal and postnatal mice and rats, and it fits within a neonatal incubator. By using predominantly off-the-shelf and 3D printed components, and a microcontroller, this treadmill was low cost and easy to reproduce. The design also included variable incline, and a transparent belt and enclosures for video and gait analysis. A touchscreen interface provided user-friendly control over belt speed and run time. Moreover, validation experiments showed high accuracy in belt speed control, allowing for tightly regulated experimental conditions. Overall, this new low-cost, open-source, variable speed and incline treadmill can be used to advance understanding of neonatal locomotion, and neuromuscular and musculoskeletal development.